STRATEGI KAMPANYE PELESTARIAN LINGKUNGAN PADA AKUN INSTAGRAM GERAKAN PEDULI SUNGAI TEMBUNG (@gps.tembung) - Nadia Syafitri (ADISAM PUBLISHER, 2024)
Environmental preservation cannot only be carried out by every organization, but environmental conservation should involve all levels of society. Many people no longer care about nature, so many people still throw it into rivers or other areas and people also don't understand the impact of throwing rubbish carelessly. Indonesia is ranked third as the country that produces the most waste in the world. Now the river care movement community is campaigning for environmental preservation by educating the public about the dangers of throwing rubbish into rivers. Through this research entitled